Susceptibilidad antimicrobiana de Staphylococcus aureus proveniente de chorizo elaborado artesanalmente. - Orbegoso Noriega, Marietta Victoria Layli (2016)
Antimicrobial susceptibility was evaluated of Staphylococcus aureus from sausage hand-crafted, for which 20 crops were reactivated and prepared bacterial turbidity equivalent to a 0.5 tube of inoculants nephelometer Mac Farland evaluated; then seeded by surface with sterile swabs on Muller-Hinton agar and antibiotic discs were placed: vancomycin, rifampin, ciprofloxacin, doxycycline, ampicillin, clindamycin, erythromycin and gentamicin in each plate , incubated at 37 °C for 18 hours ; subsequently, the halos of growth inhibition were measured in millimeters and the degree of susceptibility (sensitive, resistant and medium) was determined with reference to the table qualification standards NCCLS, 2000. After processing the data obtained, it was observed that 100% of cultures were susceptible to vancomycin, gentamicin, erythromycin, rifampicin, ciprofloxacin and doxycycline. While 90% of cultures were sensitive to ampicillin, and 10% were resistant. Likewise, 55% of crops were sensitive to clindamycin, and 45% had intermediate susceptibility. Keywords: antimicrobial susceptibility, Staphylococcus aureus, sausage.